2020
DOI: 10.3390/toxins12120794
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Ameliorates the T-2 Toxin-Triggered Intestinal Impairment in Mice by Inhibiting Inflammation and Mucosal Barrier Dysfunction through the NF-κB Signaling Pathway

Abstract: T-2 toxin, a trichothecene mycotoxin produced by Fusarium, is widely distributed in crops and animal feed and frequently induces intestinal damage. Betulinic acid (BA), a plant-derived pentacyclic lupane-type triterpene, possesses potential immunomodulatory, antioxidant and anti-inflammatory biological properties. The current study aimed to explore the protective effect and molecular mechanisms of BA on intestinal mucosal impairment provoked by acute exposure to T-2 toxin. Mice were intragastrically administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The NF-κB pathway is the main signalling pathway involved in secondary immune responses to various stimuli and the main pathway involved in intestinal inflammation [ 12 , 13 ]. These proinflammatory factors contribute to the stimulation of protective immune responses, leading to the development of excessive systemic inflammatory reactions and causing inflammatory lesions [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NF-κB pathway is the main signalling pathway involved in secondary immune responses to various stimuli and the main pathway involved in intestinal inflammation [ 12 , 13 ]. These proinflammatory factors contribute to the stimulation of protective immune responses, leading to the development of excessive systemic inflammatory reactions and causing inflammatory lesions [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…BA has been found to interfere with N‐linked glycan modifications of intercellular adhesion molecule‐1 in human lung carcinoma cells 49 . An effect on secretion is also expected, as has been observed with both BA and ACK 50–52 . In RAW264.7 macrophages, the anti‐inflammatory action of acankoreosides (Ack‐A and ‐B, essentially) involves three major aspects, as summarized in Figure 5: (1) inhibition of NF‐κB expression and activation, (2) inhibition of the proinflammatory cytokines IL‐1β and TNF‐α at the transcriptional level (leading also to reduced secretion levels), and (3) inhibition of the secretion of HMGB1 52,53 …”
Section: Ack and Related Sapogeninsmentioning
confidence: 74%
“…Since the ingestion of contaminated products is the main entry for T-2 toxin in the organism, intestinal dysfunctions are frequently associated with T-2 toxicity. Luo et al found that pretreatment with BA ameliorated the intestinal inflammation in mice through the inhibition of the NF-κB signaling pathway, which increased the anti-inflammatory/ pro-inflammatory cytokine ratio [ 88 ]. BA pretreatment also diminished intestinal injury produced by cyclophosphamide through the same NF-κB pathway inhibition [ 89 ], suggesting that this pathway could represent a valuable target for the development of new molecules able to treat intestinal dysfunctions.…”
Section: Betulinic Acidmentioning
confidence: 99%